Body mass estimation in hominins from humeral articular dimensions. Issue 3 (11th June 2020) - Ruff, Christopher B.; Squyres, Nicole; Junno, Juho‐Antti
Abstract: Objectives: While many attempts have been made to estimate body mass in hominins from lower limb bone dimensions, the upper limb has received far less attention in this regard. Here we develop new body mass estimation equations based on humeral articular breadths in a large modern human sample and apply them to 95 Plio‐Pleistocene specimens. Materials and Methods: Humeral head superoinferior and total distal articular mediolateral breadths were measured in a morphologically diverse sample of 611 modern human skeletons whose body masses were estimated from bi‐iliac breadth and reconstructed stature. Reduced major axis regressions were used to compute body mass estimation equations. Consistency of the resulting estimates with those derived previously using lower limb bone equations was assessed in matched Plio‐Pleistocene individuals or samples. Results: In the modern reference sample, the new humeral body mass estimation equations exhibit only slightly lower precision compared to the previously derived lower limb bone equations. They give generally similar estimates for Pleistocene Homo, after accounting for the different shape of the humeral head articular surface in archaic Middle and Late Pleistocene Homo, except for distal humeral estimates for Late Pleistocene specimens, which average somewhat below lower limb estimates. Humeral equations give body mass estimates for australopiths that appear much too high, except for Australopithecus sediba . A chimpanzee‐based distal humeral articular formula appears to work well for larger australopith specimens. Discussion: The new formulae provide a more secure foundation for estimating hominin body mass from humeri than previously available equations. Abstract : Regression of body mass against humeral head superoinferior breadth in 611 Holocene humans.